Optogenetics-induced activation of glutamate receptors improves memory function in mice with Alzheimer’s disease - Ke-Wei Wang; Xiao-Lin Ye; Ting Huang; Xi-Fei Yang; Liang-Yu Zou (Neural Regeneration Research, 2019)
Optogenetics is a combination of optics and genetics technology that can be used to activate or inhibit specific cells in tissues. It has been used to treat Parkinson’s disease, epilepsy and neurological diseases, but rarely Alzheimer’s disease. Adeno-associated virus carrying the CaMK promoter driving the optogenetic channelrhodopsin-2 (CHR2) gene (or without the CHR2 gene, as control) was injected into the bilateral dentate gyri, followed by repeated intrahippocampal injections of soluble low-molecular-weight amyloid-β1–42 peptide (Aβ1–42). Subsequently, the region was stimulated with a 473 nm laser (1–3 ms, 10 Hz, 5 minutes). The novel object recognition test was conducted to test memory function in mice. Immunohistochemical staining was performed to analyze the numbers of NeuN and synapsin Ia/b-positive cells in the hippocampus. Western blot assay was carried out to analyze the expression levels of glial fibrillary acidic protein, NeuN, synapsin Ia/b, metabotropic glutamate receptor-1a (mGluR-1a), mGluR-5, N-methyl-D-aspartate receptor subunit NR1, glutamate receptor 2, interleukin-1β, interleukin-6 and interleukin-10. Optogenetic stimulation improved working and short-term memory in mice with Alzheimer’s disease. This neuroprotective effect was associated with increased expression of NR1, glutamate receptor 2 and mGluR-5 in the hippocampus, and decreased expression of glial fibrillary acidic protein and interleukin-6. Our results show that optogenetics can be used to regulate the neuronal-glial network to ameliorate memory functions in mice with Alzheimer’s disease. The study was approved by the Animal Resources Committee of Jinan University, China (approval No. LL-KT-2011134) on February 28, 2011.